Fireplaces supporting central heating - Adamczyk, Jerzy (Budownictwo i Architektura / Civil and Architectural Engineering, 2013)
Article presents usage of fireplaces with a water jacket and with an air turbine in a single-family detached home. Influence of usage of fireplaces on primary energy demand was also analysed.